2010
DOI: 10.1007/s11426-010-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure study of 2′-Se-adenosine-derivatized DNA

Abstract: The selenium derivatization of nucleic acids is a novel and promising strategy for 3D structure determination of nucleic acids. Selenium can serve as an excellent anomalous scattering center to solve the phase problem, which is one of the two major bottlenecks in macromolecule X-ray crystallography. The other major bottleneck is crystallization. It has been demonstrated that the incorporated selenium functionality at the 2′-positions of the nucleosides and nucleotides is stable and does not cause significant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
(65 reference statements)
1
18
0
Order By: Relevance
“…To further confirm that this 5-TePh modification does not cause obvious structure perturbations, we have carried out the crystallization by using our 2′-Se modification strategy to facilitate the crystal growth ( 46–48 ). The modified DNA (5′-G- 2′-Se dU-G- Te T-ACAC-3′) was designed, synthesized and purified.…”
Section: Resultsmentioning
confidence: 93%
“…To further confirm that this 5-TePh modification does not cause obvious structure perturbations, we have carried out the crystallization by using our 2′-Se modification strategy to facilitate the crystal growth ( 46–48 ). The modified DNA (5′-G- 2′-Se dU-G- Te T-ACAC-3′) was designed, synthesized and purified.…”
Section: Resultsmentioning
confidence: 93%
“…Recent data has shown that the nature of the base of the modified nucleotide is not a determining factor for crystal growth, as enhanced crystal growth was also observed for other 2’-methylseleno-modified nucleotides (Salon et al, 2010; Sheng & Huang, 2010; Sheng, Salon, Gan, & Huang, 2010). As exhibited by DNA oligonucleotides containing embedded ribose moieties, localized A-type perturbations in overall B-type DNA oligonucleotides can be observed in solution structures, yet this mixed conformation is rarely seen in crystal structures, which favor longer-lived species.…”
Section: Resultsmentioning
confidence: 94%
“…Currently, given the emerging structural information of nucleic acids and their protein complexes, structure-based drug design will soon be at the heart of nucleic acid-targeting drug discovery. Recently, our laboratory pioneered and has developed the selenium derivatization of nucleic acid (SeNA) technologies [176][177][178][179][180][181], which have significantly facilitated crystal structure and function studies of nucleic acids and protein-nucleic acid complexes. With the continuous research efforts on chemical and structural biology of nucleic acids, the understandings on nucleic acid folding, structure, recognition and catalysis will be significantly further advanced.…”
Section: Discussionmentioning
confidence: 99%